Comparative assessment of antibacterial efficacy of aqueous extract of commercially available black, green, and lemon tea: an in vitro study - Arun, S. Dodamani; Minal, M. Kshirsagar; Karibasappa, G. N.; Prashanth, V. K.; Girija, A. Dodamani; Harish, C. Jadhav (International Journal of Health Sciences, 2017)
Objectives: The objective of this study is to determine and compare antibacterial efficacy of aqueous extracts of black, green, and lemon tea of a commercially available brand. Materials and Methods: The well-diffusion method was used to evaluate the antibacterial efficacy of commercially available black tea, green tea, and lemon tea at three different concentrations (1.5 g, 5 g, and 7.5 g) against Streptococcus mutans and Lactobacillus acidophilus. After incubation in appropriate culture medium, diameter of zone of inhibition was measured to assess the antibacterial efficacy of tea. Results: Maximum zone of inhibition was found with lemon tea (27 mm) followed by green tea (26 mm) and black tea (13 mm) against S. mutans and L. acidophilus. Zone of inhibition was highest at 7.5 g concentration (1 and half tea spoon) for lemon tea followed by green tea and black tea. Results were statistically analyzed with the analysis of variance (ANOVA). For pairwise intergroup multiple comparisons, bonferroni test was applied. The difference between black tea, green tea, and lemon tea were statistically significant (P < 0.001) at 5% of level of significance. Conclusion: Lemon tea at 7.5 g concentration was more effective followed by green tea and black tea against S. mutans and L. acidophilus.